Multidrug Resistance Tuberculosis in the Context of Co-Infection in Ethiopia: A Systematic Review and Meta-Analysis - Bezawit Kassaw Hailu; Yitayew Demessie; Abebe Tesfaye Gessese; Gashaw Getaneh Dagnaw; Haileyesus Dejene (Journal of Epidemiology and Global Health)
Abstract The rise of multidrug-resistant tuberculosis (MDR-TB) remains a critical public health challenge, particularly in developing countries like Ethiopia. This systematic review and meta-analysis aimed to estimate the pooled prevalence of MDR-TB with co-infections and assess its effects among different co-infections in Ethiopia. The systematic review and meta-analysis were conducted from August to October 2024. The study adhered to PRISMA guidelines and utilized various academic databases including PubMed, Web of Science and Science Direct to identify relevant articles. To check for publication bias and small study effects, a funnel plot and Egger’s test were employed. The statistical analysis was performed with R software version 4.4.1. From an original pool of 6,461 papers, 15 studies published between 2014 and 2024 were considered after applying certain inclusion and exclusion criteria. The analysis revealed an overall pooled prevalence of MDR-TB in the context of co-infections at 20% (95% CI: 14.0–26.0). Notably, the prevalence was higher among individuals with HIV co-infection at 23.2% (95% CI: 18.3–28.0), while it was lower in those with diabetes co-infection at 10% (95% CI: 3.0-17.3). The study found significant heterogeneity among the reported prevalence rates (I² = 94.93%, p < 0.001). These findings highlight the complex interplay between MDR-TB and other co-infections, posing significant challenges for clinical management and public health in Ethiopia. To enhance health outcomes and curb the spread of MDR-TB, government and public health authorities must implement targeted interventions, including monitoring and treatment programs in high-prevalence areas.